2013
DOI: 10.1111/adb.12034
|View full text |Cite
|
Sign up to set email alerts
|

Relation between corticosterone and fear‐related behavior in mice selectively bred for high or low alcohol preference

Abstract: Blunted cortisol responses to stress or trauma have been linked with genetic (familial) risk for both alcoholism and post-traumatic stress disorder (PTSD). Mouse lines selectively bred for high (HAP) or low (LAP) alcohol preference may be a relevant model of genetic risk for co-morbid alcoholism and PTSD in humans. HAP mice show greater fear-potentiated startle (FPS), a model used to study PTSD, than LAP mice. The relation between corticosterone (CORT) and FPS behavior was explored in four experiments. Naïve m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
27
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 50 publications
8
27
1
Order By: Relevance
“…However, lower corticosterone levels and a blunted corticosterone response to stress are typical hallmarks of PTSD (Chester et al, 2013; Zoladz and Diamond, 2013), which more closely resembles the endocrine findings in our H-FSS mice. The hypothesis that H-FSS mice suffer from a condition resembling PTSD or a principal fear disorder can be tested with a thorough analysis of the HPA axis, e.g., by presenting various stressors and measuring hormone levels at different time points following acute stress exposure and/or delivery of chronic stressors known to provoke PTSD symptoms in rodent models.…”
Section: Discussionsupporting
confidence: 85%
“…However, lower corticosterone levels and a blunted corticosterone response to stress are typical hallmarks of PTSD (Chester et al, 2013; Zoladz and Diamond, 2013), which more closely resembles the endocrine findings in our H-FSS mice. The hypothesis that H-FSS mice suffer from a condition resembling PTSD or a principal fear disorder can be tested with a thorough analysis of the HPA axis, e.g., by presenting various stressors and measuring hormone levels at different time points following acute stress exposure and/or delivery of chronic stressors known to provoke PTSD symptoms in rodent models.…”
Section: Discussionsupporting
confidence: 85%
“…This finding, which is similar to results reported in humans with a family history of AUDs (Sher & Levenson, 1982; Sinha, Robinson, & O’Malley, 1998), suggested that greater sensitivity to the anxiolytic, and therefore, reinforcing, effects of alcohol in people with a genetic propensity toward AUDs may be one of the mechanisms that contributes to the high rate of co-morbidity between AUD and PTSD. These mouse lines also show differences in the HPA axis response to stress (lower corticosterone levels after foot shock and fear-related cues) that correlate with their genetically influenced divergent alcohol-drinking behavior (Chester et al, 2014), and match data reported in humans with PTSD (Yehuda, 2001) and in other rodent models of PTSD-like behavior (Cohen et al, 2006). Overall, our data in these lines suggest they are a unique model for identifying genetic and biological factors that contribute to AUD and PTSD comorbidity in humans.…”
Section: Introductionsupporting
confidence: 77%
“…Alcohol-naïve HAP lines (1 and 2) show greater fear potentiated startle (FPS), a model for fear-related disorders such as PTSD, compared to LAP lines (Barrenha & Chester, 2007; Barrenha, Coon, & Chester, 2011; Chester, Kirchhoff, & Barrenha, 2014). Fear-conditioning models such as FPS are commonly used to study mechanisms that contribute to fear-related disorders such as PTSD (Kim & Jung, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the significant overlap between the underlying mechanisms, fear conditioning in rodents is commonly used to study aspects of anxiety and fear-related disorders, such PTSD (Chester, Kirchhoff, & Barrenha, 2013; Kim & Jung, 2006). Several paradigms of inescapable shock delivery in unpredictable patterns have been shown to create PTSD-like states in rodents (Foa, Zinbarg, & Rothbaum, 1992; Maier, 2001; Siegmund & Wotjak, 2007), and prior exposure to multiple shocks enhances the subsequent learning of conditioned fear (Rau, DeCola, & Fanselow, 2005).…”
Section: Ptsd: a Disease Of Stress And Learning That Shows High Comentioning
confidence: 99%
“…Alcohol also has well-documented effects on several forms of learning and memory, including fear-conditioned behaviors (Alijan-pour et al, 2012; Weissenborn & Duka, 2003; Alijan-pour et al, 2012). Genetic rodent models for drinking also show distinctive phenotypes for fear-conditioned behaviors, such as FPS (Barrenha, Coon, & Chester, 2011; Chester et al, 2013). This suggests that common genes regulate alcohol preference and the propensity toward fear-related behavior, thus implicating a shared underlying mechanism in these processes.…”
Section: Alcohol and Fear Conditioningmentioning
confidence: 99%